2014
DOI: 10.1021/ja5082712
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Apparent Conflicts between Theoretical and Experimental Models of Phosphate Monoester Hydrolysis

Abstract: Understanding phosphoryl and sulfuryl transfer is central to many biochemical processes. However, despite decades of experimental and computational studies, a consensus concerning the precise mechanistic details of these reactions has yet to be reached. In this work we perform a detailed comparative theoretical study of the hydrolysis of p-nitrophenyl phosphate, methyl phosphate and p-nitrophenyl sulfate, all of which have served as key model systems for understanding phosphoryl and sulfuryl transfer reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
206
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(225 citation statements)
references
References 74 publications
18
206
0
1
Order By: Relevance
“…We previously suggested that in the absence of metal ions, the preferred pathway for the hydrolysis of phosphate monoesters with good leaving groups is one involving a loose, dissociative transition state [19,20]. We demonstrate that for both compounds studied here, the presence of magnesium ions increases the energetic difference between substrate-and solvent-assisted pathways, creating a greater preference for a solventassisted pathway than in the absence of the metal.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…We previously suggested that in the absence of metal ions, the preferred pathway for the hydrolysis of phosphate monoesters with good leaving groups is one involving a loose, dissociative transition state [19,20]. We demonstrate that for both compounds studied here, the presence of magnesium ions increases the energetic difference between substrate-and solvent-assisted pathways, creating a greater preference for a solventassisted pathway than in the absence of the metal.…”
Section: Introductionmentioning
confidence: 55%
“…[7,8] and references cited therein). To partially address this issue, we recently performed detailed comparisons of a range of phosphate monoester dianions with different leaving groups, examining both leaving group effects and the effect of including explicit microsolvation in the calculations [19,20]. In addition to reasonable quantitative agreement between experimental and calculated activation free energies, our calculations reproduced both the linear free energy relationship for phosphate monoester dianion hydrolysis, as well as the experimentally observed kinetic isotope effects for p-nitrophenyl phosphate hydrolysis [19].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations